2020 ASEE Virtual Annual Conference Content Access Proceedings
DOI: 10.18260/1-2--34220
|View full text |Cite
|
Sign up to set email alerts
|

Blended Statics: Finding an Effective Mix of Traditional and Flipped Classrooms in an Engineering Mechanics Course

Abstract: is a graduate student and teaching assistant in the department of Mechanical Engineering and the department of Mathematics at the University of Maine. His current research includes multiscale modeling of nanomaterials to study their mechanical behavior using atomistic and first-principles computational techniques coupled with nonlinear elasticity. Before joining the University of Maine, Serge pursued his undergraduate studies at the University of Balamand (Lebanon) where he worked on the mechanics of lamina co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Many studies have shown that students and instructors appreciate the level of engagement they had during the problem-solving sessions in the blended teaching 4,3,5 . The same thing should be applied to the online learning.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that students and instructors appreciate the level of engagement they had during the problem-solving sessions in the blended teaching 4,3,5 . The same thing should be applied to the online learning.…”
Section: Resultsmentioning
confidence: 99%
“…Many instructors who have built flipped classrooms have done so slowly and are continuously refining their courses. This has resulted in the "blended" or "mixed-mode" flipped class where part of the content is covered in class and part is covered virtually [14], [15]. This allows for a more seamless transition for students and instructors from traditional lecture style in-class format to a more active classroom environment.…”
Section: Flipped Civil Engineering Classesmentioning
confidence: 99%
“…While this trend towards minimizing instructor involvement has its benefits, there are some potential drawbacks [11][12][13][14]. For instance, some students may struggle with self-learning, and potentially get behind the course flow.…”
Section: Introductionmentioning
confidence: 99%